The two most common swimming faults, part 2 - Woolley, H.
This article will teach you important fundamentals of swimming technique and change the way you think about swimming forever. These two faults revolve around two commonly discussed concepts in swimming, that of 1.correct body position and 2.shoulder extension. In this article we will discuss the second of these two concepts in greater detail (shoulder extension & rotation,reach & roll, flexibility).